2010
DOI: 10.1007/s00424-010-0905-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutant human β4 subunit identified in amyotrophic lateral sclerosis patients impairs nicotinic receptor function

Abstract: Recently identified mutations in the genes encoding the neuronal nicotinic ACh receptor (nAChR) subunits in patients affected by sporadic amyotrophic lateral sclerosis (sALS) may represent a factor which enhances disease susceptibility, in particular in association with ambient causes such as cigarette smoking. In this work, we characterize the functional properties of nAChRs containing the β4R349C subunit, the mutation most frequently encountered in sALS patients. The mutation was coexpressed with wild-type α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
(36 reference statements)
3
11
0
Order By: Relevance
“…We observed that two variants (red bars, Figure 1) significantly differed from α3β4 control currents. These were the β4 R348C variant (corresponding to the human R349C) which showed significantly reduced currents (0.12 ± 0.43 normalized amplitude increase) in agreement with previous reports (Moriconi et al, 2011; Richards et al, 2011), and the D447Y variant (corresponding to the human D444Y) that showed significantly larger currents (3.13 ± 0.24 normalized amplitude increase). This rare SNP reported by Weiss and colleagues (Weiss et al, 2008) has not been previously characterized functionally.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…We observed that two variants (red bars, Figure 1) significantly differed from α3β4 control currents. These were the β4 R348C variant (corresponding to the human R349C) which showed significantly reduced currents (0.12 ± 0.43 normalized amplitude increase) in agreement with previous reports (Moriconi et al, 2011; Richards et al, 2011), and the D447Y variant (corresponding to the human D444Y) that showed significantly larger currents (3.13 ± 0.24 normalized amplitude increase). This rare SNP reported by Weiss and colleagues (Weiss et al, 2008) has not been previously characterized functionally.…”
Section: Resultssupporting
confidence: 92%
“…Quantitation of average current amplitudes revealed that the β4 point mutants A90I, T374I, and D447Y exhibited significantly larger responses to nicotine and that the R348C variant led to reduced nicotine-evoked current amplitudes, when compared to native α3β4 responses (Figure 4B). These results confirmed our electrophysiological studies in oocytes (Figure 1) and whole-cell recordings in transfected cells (Moriconi et al, 2011; Haller et al, 2012). …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The authors tested the T91I, R136W, S140G and M467V variants, and found relatively small changes in the EC 50 for ACh of a similar magnitude and direction to our observations. The second study examined the properties of the R349C variant, expressed in GH4C1 cells [33]. In this study, a relatively large increase in the EC 50 for ACh was found when the variant was expressed with the α3 subunit (3.2-fold) in comparison to our modest decrease (to 0.7-fold).…”
Section: Discussionmentioning
confidence: 82%